2005
DOI: 10.1139/g04-095
|View full text |Cite
|
Sign up to set email alerts
|

Efficient genetic transformation of Sorghum using a visual screening marker

Abstract: To transform grain sorghum (Sorghum bicolor (L.) Moench) with a visual reporter gene (gfp) and a target gene (tlp), three genotypes (two inbreds, Tx 430 and C401, and a commercial hybrid, Pioneer 8505) were used. We obtained a total of 1011 fertile transgenic plants from 61 independent callus lines, which were produced from 2463 zygotic immature embryos via Agrobacterium-mediated transformation. The reporter gene, gfp, encoding green fluorescent protein (GFP), was used as a visual screening marker, and the tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Agrobacterium is a potent transformation tool with the advantage of producing transgenic plants with low transgene copy number. In the present study, the low transgene copy number is consistent with other investigations using Agrobacterium on cereals (Hiei et al, 1994;Ishida et al, 1996;Cheng et al, 1997;Zhao et al, 2000;Gao et al, 2005a;Lu et al, 2009).…”
Section: Analysis Of the Transgenic Plantssupporting
confidence: 93%
See 2 more Smart Citations
“…Agrobacterium is a potent transformation tool with the advantage of producing transgenic plants with low transgene copy number. In the present study, the low transgene copy number is consistent with other investigations using Agrobacterium on cereals (Hiei et al, 1994;Ishida et al, 1996;Cheng et al, 1997;Zhao et al, 2000;Gao et al, 2005a;Lu et al, 2009).…”
Section: Analysis Of the Transgenic Plantssupporting
confidence: 93%
“…Selection of bialaphos-resistant callus is often conducted at 2 to 3 mg/L bialaphos (Casas et al, 1993;Frame et al, 2002;Grootboom et al, 2010). Bialaphos, as selection agent, has been found to hinder regeneration capacity of sorghum (Casas et al, 1993;Gao et al, 2005a;Lu et al, 2009;Grootboom et al, 2010). In the present investigation, bialaphos imposed a severe selection on sorghum callus.…”
Section: Sorghum Transformation and Regenerationmentioning
confidence: 72%
See 1 more Smart Citation
“…In sorghum the visual marker genes green fluorescent protein (gfp) and β-glucuronidase (GUS) are each effective in monitoring for transgenic cells (Jeoung et al 2002). Using the former visual marker Gao et al (2005a) reported a 3.0% transformation efficiency as means to monitor for transgenic differentiating cell lineages from immature embryos of sorghum.…”
Section: Sorghum Transformationmentioning
confidence: 99%
“…The PMI structural gene (manA) of Escherichia coli, which is capable of converting mannose to fructose, has been used as a selectable marker gene. The conversion of mannose to a metabolizable fructose carbon source which is beneficial to plants was achieved in sorghum with Agrobacteriummediated system using manA gene (Gao et al, 2005a;Gurel et al, 2009). …”
Section: Nutrient Selection Markermentioning
confidence: 99%